Diseño arquitectónico de centro de rehabilitación psicotrópica para adolescentes de la ciudad de Guayaquil - Cuascota Tanicuchi, Jimmy Paúl (2018)
The project was established evaluating the lack of rehabilitation centers in the city of Guayaquil. The intention is proposing a new project that covers the current demand. There is a deficient service of rehabilitation for the adolescence plunged in the addiction to psychotropic substances, besides that it is in terrible condition and breaking the demanded norms….